PENGARUH ASSETS DAN LIABILITIES TERHADAP NET PROFIT PADA PERUSAHAAN RETAIL YANG TERDAFTAR DI BEI TAHUN 2019-2024 - Juan Hadi Saputra; Suryanto Nahrul Sosrowidigdo (Jurnal Akuntansi, 2024)
A company not only records the financial reports received and issued during a certain period, but also maintains the common goal of making a profit. Company profits can be concluded from various points of view, one of which is from the company's net profit. Net profit is profit that has been previously deducted. Data processing methods are methods used in conducting research in order to obtain a conclusion from the research conducted. Judging from the framework of thought and explanation that has been presented previously, the technique used in conducting this research is quantitative analysis. In this research, the analysis used to determine the effect of total assets and total liabilities on the company's net profit uses descriptive statistical tests, classical assumption tests, t tests, f tests, and coefficient of determination tests. If the variable significance value is lower than the specified significance level, namely less than 0.05, then it can be concluded that total assets partially have a significant influence on net profit. If the sig value of the variable is upper than the specified significance level, it can be concluded that total liabilities do not affect the company's net profit. This means that total assets have a significant influence on the company's net profit, while total liabilities do not have a significant influence. However, both simultaneously have the effect of the net profit obtained by the company.